New York unearths paleotech relic [subway signal system]. - Jones, W.D.
On January 25, 2005, a fire knocked out a subway line serving large sections of Manhattan, Brooklyn, and Queens. The fire exposed a signal room containing some 600 electromechanical relays as well as signal wires, crucial components of a fixed-block signaling system that has kept proper headway between trains since the New York city subway system was inaugurated. The relic devices were retained because they worked, though not well, and upgrades would have been lost on commuters. Further, a new design could not be implemented without disrupting the system. Nevertheless, a six-year US 288 million investment has been planned for the modernization of the subway system. The plan involves computerization of train operations that will no longer require a conductor or train operator to maintain speed, open and close doors, or control its route.
Keywords: New York city subway system; Computerized train operations; Electromechanical relays; Fixed-block signaling system; Legacy technology; Modernization; Relic devices